IMPLEMENTASI PEMBELAJARAN BAHASA ARAB BERBASIS E-LEARNING - Yayah Robiatul Adawiyah (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Abstract The development of computerized systems through networks is increasing. The internet is a public network. Its existence is indispensable both as a medium of information and free communication. One of the uses of the internet is the distance learning system through electronic learning or better known as E-Learning. This type of research is a descriptive qualitative research with a field research approach (Field Research). Arabic language lectures at Nurul Jadid Paiton University are conducted using E-learning media in Arabic and non-language study programs. The results showed that the E-learning application can help facilitate lecturers and students in carrying out the learning process more deeply. This is because both students and lecturers can collect assignments, distribute assignments, assess assignments at home or anywhere without being bound by time limits or class hours. Keywords: Implementation, Learning, Arabic, E-learning